Histopathological atlas of desmoplastic reaction characterization in colorectal cancer - Ueno, Hideki (Jpn J Clin Oncol, 2021)
Emergent scientific evidence indicates the central role of cancer-associated fibroblasts in determining whether the microenvironment of cancer works as friend or foe of the host; however, there is no unified histological evaluation framework of fibrotic stroma in colorectal cancers. Myxoid stroma and keloid-like collagen are site-specific histopathological features generated by cancer-associated fibroblasts, which appear exclusively in the tumor front during desmoplastic reaction. On the basis of these two stromal components, desmoplastic reaction is categorized into three patterns—immature, intermediate and mature—using hematoxylin and eosin staining. In January 2020, a prospective randomized clinical trial, JCOG1805, to elucidate the value of adjuvant chemotherapy in stage II colorectal cancer patients with pathological risk factors of recurrence was launched in Japan, in which intermediate/immature desmoplastic reaction is one of the four risk factors selected as inclusion criteria. This paper covers the diagnostic criteria for the desmoplastic reaction classification being used in the JCOG1805 study.